Geopolitical risks and the predictability of regional oil returns and volatility. (19th July 2019) - Demirer, Riza; Gupta, Rangan; Ji, Qiang; Tiwari, Aviral Kumar
Abstract: This paper hypothesises that global geopolitical risks (GPRs) can predict oil market return and volatility. For our purpose, we use a k ‐th order non‐parametric causality‐in‐quantile test, applied to a daily data set covering the period of 15 May 1996 to 31 May 2018 of six oil benchmarks (the Nigerian Bonny Light, Brent, Dubai, OPEC Reference Basket (ORB), Tapis and WTI). Our results indicate that the relationship between oil returns and GPRs is highly non‐linear, and hence, linear tests of Granger causality cannot be relied upon. Based on the data‐driven econometric method, we observe that GPRs have predictability for oil returns of the West African Bonny Light, ORB and Tapis, while in terms of volatility, causality is observed for all oil prices barring the case of Dubai. In sum, the impact of GPRs is primarily on volatility of oil markets, but more importantly, the impact of GPRs is not uniform across the oil markets.